Taṭwīr al-Wasāil al-Muta‘addidah al-Tafā‘uliyyah bi Istikhdāmi al-Wasīlah al-Iliktrūniyyah li Ta’līm al-Lughah al-‘Arabiyyah - Mujahidatul Aliah; Ahmad Maghfurin (Alsina : Journal of Arabic Studies, 2019)
Lack of use of multimedia influences the lack of students' desire to learn Arabic and their difficulty in understanding. Teacher-centered Arabic teaching contradicts the nature of students with an audiovisual learning model. As a remedy for this problem, we have developed a variety of methods for teaching Arabic with the help of the Power Point Program. It was implemented at the National Islamic High School in Dorongan-Semarang. This research is evolutionary using the DDD-E model, which consists of four steps, namely, designation (Decide) and design (Design) and development (Development) and evaluation (Evaluate). Assessment of the quality of the means is based on the correction of the experts in Article (80%) and teaching methods (84%). To assess the validity of their use we rely on the response of students (80%). The effectiveness of their use is based on the results of the students in the test (64%), and they are 18 students in the eleventh grade selected by purposeful technology.